Inheritance of resistance to tomato late blight in a population of Solanum lycopersicum x Solanum habrochaites. - Elsayed, Ahmed Youssef Abdelnabi Mohamed (2010)
Late blight caused by Phytophthora infestans (Mont.) De Bary, is a serious disease affecting tomato production worldwide especially in tropical and subtropical regions. In Brazil, about 20% of the tomato production cost is due to the chemical control of late blight. The absence of tomato cultivars resistant tothis disease is related to the high variability of the pathogen and the quantitative inheritance of the resistance. In the development of competitive cultivars, estimating the combining ability is extremely important to assist the breeder in the choice of parents and hybrid combinations. The aim of this researchwas to study the inheritance of late blight resistance in both fresh and processing tomatovarieties through analysis of inheritance in both half-diallel and F2 segregant populations. A half-diallel set of crosses was generated from ten diverse parents comprising two groups, I and II as varieties and testers, respectively. The first group included three commercial tomato hybrids 'Ikram', 'Alambra F1' and 'Heinz H7155', that were considered as susceptible in the current study and two resistant varieties NC1 CELBR and NC2 CELBR possessing Ph-2 and Ph-3resistant genes to late blight. Group II (testers) included five inbred lines derived from the interspecific cross S. lycopersicum L. cv. Santa Clara x S. habrochaites f. glabratum accession BGH 6902. The parents and F1 crosses in addition to two standard susceptible varieties 'New York' and 'Caline' processing Ph-1 resistance gene were artificially inoculated with mixed isolates of Phytopthora infestans in a field experiment. The hybrid combinations were evaluated for resistance to late blight and fruit quality in two simultaneous experiments, in a randomized block design with three replications. The plants were inoculated with a mixture of sporangia of P. infestans at concentration 103 sporangia.mL-1. Disease severity was determined by estimating three disease variables: severity at halfway epidemic (Y50), severity at the end of the epidemic (Ymax) and area under disease progress curve (AUDPC). The following characteristics were determined for fruit quality: average fruit weight, fruit size, fruit size index, pH, % titratableacidity, total soluble solids, firmness and flavor. Analysis of variance showed high significant differences among the genotypes for the three parameters and strong positive correlation (0.949) was observed among the disease variables Y50, Ymax and AUDPC. Both the additive and non-additive genetic effectscontributed in controlling the resistance. Predominance of GCA effects suggested that additive effects were more important than non-additive effects and that simple selection or backcrossing would be useful for improving the resistance in these varieties. The best donor parents for resistance to late blight were cultivars NC 2 CELBR and NC 1 CELBR (Group I) and 133A and 163A (Group II). The best combinations were NC 2 CELBR x 64B and NC 1 CELBR x 64B. However, the parents selected for resistance to late blight were inferior in terms of fruit quality especially the parents of Group II. The cross CELBR NC 2 x 163A was the most suitable for intra- population breeding programs to late blight. It is worth mentioning that all the five inbred lines were highly stable with respect to late blight resistance, confirming the presence of polygenic resistance. The genetic analysis of the resistance in the F2 population indicated that resistance is inherited as a partially recessive trait. The heterosis scores were 32.97 and 26.76, respectively for the two populations whereas HEN4 was more resistant to P. infestans than IKR4 population. Most fruit quality traits had significant variation in both GCA and SCA except for pH and titratable acidity, where no significant difference was observed. Both the additive and non-additive genetic effects were included in controlling these traits. The inbred line 163A proved its superiority with regard to AFW, FS, pH and firmness when compared to other lines. The enetic analysis of the inheritance to resistance indicated that the resistance in the inbred lines was controlled by recessive genes. Hence, only the best parents of group I could be selected based on general combining ability. Whereas, selection based on specific combining ability could be a viable option for selecting the segregating generation to avoid losing the recessive resistant genes that exit in the advanced inbred lines.